Response of maize growth and soil biological characteristics to planting density under fertigation in a semi-arid region - Jiang, Peng; Li, Lei; Xu, Dejia; Wang, Rui; Sun, Quan (International Journal of Agricultural and Biological Engineering, 2024)
Increasing the planting density can exacerbate crop competition for water, nutrients and space which results in a decline in the crop yields. However, the effect of increasing planting density on crop growth and soil biological characteristics in barren sandy land in the semi-arid regions are still unclear. In this study, we investigated the effects of six planting densities (5.4×104, 6.45×104, 7.95×104, 9.5×104, 9.75×104 and 10.5×104 plants/hm2) on maize growth, photosynthesis characteristics, yield and soil biological characteristics in barren sandy soil in the semi-arid region of Ningxia, China. The results indicated that the stem diameter and spike length decreased linearly with increasing planting density. The plant height, spike weight, grain weight and 100-grain weight decreased with increasing plating density. Moreover, the root length increased with increasing planting density. The diameter, volume and activity increased and then decreased with increasing planting density. There was no significant difference (p>0.05) in the effect of planting density on transpiration rate intercellular CO2 concentration. As well, the soil microbial biomass carbon and microbial biomass nitrogen decreased with increasing planting density. The soil catalase activities increased and then decreased with increasing planting density. The alkaline phosphatase activity, the amounts of soil bacteria and actinomycetes increased with increasing planting density. Generally, a moderately increasing planting density can improve maize yield when water and nutrients are sufficient. The optimal planting density was 8.29×104 plants/hm2 and the highest yield was 15.84 t/hm2 in barren sandy soil in semi-arid region of Ningxia, China. This study provides a theoretical basis for high yield and high efficiency of maize. Key words: maize growth, planting density, yield, fertigation, soil enzyme activity DOI: 10.25165/j.ijabe.20241702.8090 DOI: 10.25165/j.ijabe.20241702.8090 Citation: Jiang P, Li L, Xu D J, Wang R, Sun Q. Response of maize growth and soil biological characteristics to planting density under fertigation in a semi-arid region. Int J Agric & Biol Eng, 2024; 17(2): 186–192.